2003
DOI: 10.1007/s10096-003-1004-5
|View full text |Cite
|
Sign up to set email alerts
|

Virus Isolation for Diagnosing Dengue Virus Infections in Returning Travelers

Abstract: Dengue fever is recognized as one of the most frequent imported acute febrile illnesses affecting European tourists returning from the tropics. In order to assess the value of virus isolation for the diagnosis of dengue fever, 70 cases of dengue fever confirmed in German travelers during the period 1993-2001 were analyzed retrospectively. In 26 patients who had developed acute febrile illness within 2 weeks following their return from a trip to a dengue-endemic area, 9 of 13 attempts to isolate the virus were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Keywords Candida albicans, Candida krusei, chlorhexidine, chloroxylenol, impregnated devices, rabbit model Candida spp. are recognised increasingly as important causes of infection associated with medical devices [1]. Recent surveillance data from 49 hospitals indicated that Candida spp.…”
Section: Research Notementioning
confidence: 99%
See 4 more Smart Citations
“…Keywords Candida albicans, Candida krusei, chlorhexidine, chloroxylenol, impregnated devices, rabbit model Candida spp. are recognised increasingly as important causes of infection associated with medical devices [1]. Recent surveillance data from 49 hospitals indicated that Candida spp.…”
Section: Research Notementioning
confidence: 99%
“…Dengue fever (DF) is among the most important arthropod‐borne virus diseases in terms of human morbidity and mortality. The spectrum of this disease, caused by the four distinct dengue virus serotypes, DEN‐1 to DEN‐4, ranges from a self‐limiting febrile illness (DF) to dengue haemorrhagic fever/dengue shock syndrome (DHF/DSS) [1]. With c. 2.5 billion people living in endemic areas, there are 50–100 million cases of dengue fever and 250 000–500 000 cases of DHF/DS with 24 000 deaths, annually [2].…”
Section: Detection Of Dengue Virus Rna By Rt‐pcr At Various Time‐poinmentioning
confidence: 99%
See 3 more Smart Citations